Marketing Strategy In Penetrating The Premium Laptop Segment And Strengthening The Brand Study Case Of PT. Acer Indonesia - Surya Dewati, Okky; Ashari Nasution, Reza (The Indonesian Journal of Business Administration, 2017)
Abstract - PT. ACER Indonesia, is one of the IT products company which producing PC, Notebooks, Projector, Desktop, and AIO products. The company has been well known in Indonesia with ACER brand, as the producer of mass products Notebook. Most of the well – known products from ACER are the middle – low products with Celeron and Pentium processor. As the increment trend shows since early 2016, company is converting its business focus to the premium segment laptop. This thesis is an initial scientific attempt to determine the marketing strategy in order to penetrating and strengthening the brand in the premium segment market share. The project study used in this thesis is ACER premium product line up, which are ACER Switch Alpha 12, ACER E5-475G Core i7, ACER Swift 3, ACER SPIN 5, ACER Swift 7, and ACER Spin 7. Writer will identify the marketing and branding strategy that currently apply to those products and further identify the results in the market which reflected from the market survey and also market share data from GfK Retail and Technology, which finally can concluded the solution to penetrate and strengthen the brand in the premium market segment. As a result of the research, it was determined that ACER has already manufactured the right products to compete in the premium market segment. However market still have low knowledge regarding brand’s premium line up and ACER brand recall is still correlating the brand as the strong player in the medium – low laptop market. As the solution for this issue, ACER need to increase the brand equity and awareness by doing more strategic marketing activities which focusing to explore and introducing its premium products to the market. As well as the notion, the strategic marketing and branding strategy must be applied continuously to gain more awareness and recall of ACER premium products in the market. Keywords: Premium, Laptop, IT Products, Brand Marketing,